Neural Entrainment and Sensorimotor Synchronization to the Beat in Children with Developmental Dyslexia: An EEG Study - Colling, Lincoln J.; Noble, Hannah L.; Goswami, Usha (Frontiers in Neuroscience, 2017)
Tapping in time to a metronome beat (beat synchronization) shows considerable variability in child populations, yet individual differences in beat synchronization are reliably related to reading development. Children with developmental dyslexia show impairments in beat synchronization. These impairments may reflect deficiencies in auditory perception of the beat which in turn affect auditory-motor mapping, or may reflect an independent motor deficit. Here we used a new methodology in EEG based on measuring beat-related steady-state evoked potentials (SS-EPs, Nozaradan et al., 2015) to disentangle neural sensory and motor contributions to behavioural beat synchronization in children with dyslexia. Children tapped with both their left and right hands to every second beat of a metronome pulse delivered at 2.4 Hz, or listened passively to the beat. Analyses of preferred phase in EEG showed that the children with dyslexia were overall significantly less accurate than control children in neural beat synchronization. Regarding SS-EPs, the groups differed for the passive Auditory listening condition only. The data suggest that neural rhythmic entrainment is atypical in children with dyslexia for both an auditory beat and during sensori-motor coupling (tapping). The data support the literature suggesting that rhythm-based interventions help children with developmental disorders of language learning, across languages.